Diagnostic Accuracy of Synovial Neopterin, TNF-α and Presepsin in Periprosthetic Joint Infection: A Prospective Study - Busch, André; Jäger, Marcus; Engler, Harald; Wasssenaar, Dennis; Bielefeld, Charlotte; Wegner, Alexander (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Background Due to the lack of specificity of conventional diagnostic tools, the prediction of periprosthetic joint infections (PJI) remains challenging. The purpose of this study was to evaluate the accuracy of synovial fluid neopterin, presepsin, and TNF-α as diagnostic parameters and to compare it to the biomarkers recommended in the 2018 definition of periprosthetic hip and knee infection.Methods Between August 2018 and July 2019, a prospective cohort study was conducted in 80 patients with painful hip, shoulder, and knee arthroplasty. In addition to medical history, clinical and laboratory data were gathered. PJI was diagnosed based on the 2018 definition of periprosthetic hip and knee infection. Synovial joint fluid was analyzed for biomarker measurement using standard quantitative enzyme immunoassay kits.Results Fifty-three patients (66%) were classified as the aseptic group and twenty-seven patients (34%) as the PJI group. The mean levels of synovial fluid neopterin were significantly higher (p < 0.01) in the PJI group than those in the aseptic group (aseptic 8.3 ± 6.9 vs. PJI 20.9 ± 21.4 nmol/L). The average values of synovial fluid TNF-α and presepsin were not significantly higher in the PJI group than those in the aseptic group (presepsin: aseptic 0.13 ± 0.19 vs. PJI 0.11 ± 0.32 ng/mL, p = 0.08; TNF-α: aseptic 6.6 ± 7.3 vs. PJI 46.3 ± 123.2 pg/mL, p = 0.17). Synovial fluid neopterin was 59% specific and 74% sensitive with a cut-off value of 7.2 nmol/L. The sensitivity and specificity of synovial fluid TNF-α were 63 and 51% with a cut-off value of 3.9 pg/mL. Synovial fluid presepsin was 51% specific and 29% sensitive with a cut-off value above 0.06 ng/mL.Conclusion Synovial fluid neopterin appears to a reliable diagnostic marker for detection of PJI. In contrast, synovial fluid TNF-α and presepsin are not suitable to exclude or diagnose PJI.
Keywords: neopterin; TNF-α; presepsin; PJI; synovial fluid